A Comprehensive Performance Analysis of Pradhan Mantri Mudra Yojana with Emphasis on Women Entrepreneurship - Bolla, Madhavi; Jahan, Masarat; Naveen Kumar, B. (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This study looks closely at how loans were given out under the Pradhan Mantri Mudra Yojana (PMMY) from 2019–20 to 2023–24, divided into three types of loans—Shishu, Kishor, and Tarun—and four social groups—General, SC, ST, and OBC. The outcomes reveal that Kishor loans regularly garnered the largest disbursements, underscoring a shift of micro-enterprises towards mid-level stability and expansion. Beneficiaries from the general category consistently outnumbered those from OBCs, SCs, and STs in loan receipts overall years. The COVID-19 pandemic caused a temporary decline in 2020–21, but a vigorous rebound ensued, showcasing the resilience of the policy. The research reveals significant variance in disbursement amounts among different socioeconomic groups and types of loans, with the General category showing the highest standard deviation. The research stresses the need for inclusive credit policy, specifically targeted at marginalised SC/ST groups via organised financial literacy and outreach initiatives.